The Urgency of Implementing Step-In Rights Clauses in Project Financing Contracts in Indonesia - Naomi Audri Klarisa Sitompul; Jevvon Suherman; Hidayat Dita Nur Faizal; Hamit Tantio Lumban Gaol; Adelina Mariani Sihombing (Recht Studiosum Law Review, 2024)
The increasing infrastructure development in Indonesia today is directly proportional to the growing need for funding to support such projects. The funding model commonly used in infrastructure development is project finance, where risk management and cost allocation are shared among the project participants. As infrastructure projects become more complex and long-term, they often face various issues such as cash flow problems and losses incurred in the event of default. These issues can actually be addressed by implementing the Step-In Rights Clause, which grants the employer the right to intervene in the work of the contractor. However, the regulation of the step-in rights clause has not yet been explicitly governed by Indonesian legislation. This paper aims to explain the urgency of applying the step-in rights clause in construction contracts. The article employs a normative legal research method with a statute approach and a conceptual approach. In practice, the application of the step-in rights clause offers many advantages and has been implemented in several countries, including Australia.